Crystal structure and Hirshfeld surface analysis of 2-{[2,8-bis(trifluoromethyl)quinolin-4-yl](hydroxy)methyl}piperidin-1-ium 2-hydroxy-2-phenylacetate hemihydrate - Wardell, James L.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The asymmetric unit of the title salt, C17H17F6N2O+·C8H7O3-·0.5H2O, comprises a pair of pseudo-enantiomeric (i.e. related by a non-crystallographic centre of symmetry) piperidin-1-ium cations, two carboxylate anions and a water molecule of crystallization. The cations have similar conformations approximating to a letter, L: one of them shows disorder of its -CF3 group over two sets of sites in a 0.775 (3):0.225 (3) ratio. Distinctive conformations are found for the anions, one with the carboxylate group lying to one side of the plane through the phenyl ring and the other where the oxygen atoms lie to either side of the plane. In the latter, an intramolecular hydroxy-O-H...O(carboxylate) charge-assisted hydrogen bond is found. The packing features extensive O-H...O,N hydrogen bonding, often charge-assisted; C-H...[pi] interactions are also formed. The hydrogen bonding results in the formation of five distinctive supramolecular synthons and assembles molecules in the ac plane. The quinolinyl rings lie to either side of the layer and inter-digitate with layers on either side, are approximately parallel to the b axis and are connected by [pi]-[pi] [inter-centroid separation = 3.6904 (18) Å] as well as C-F...[pi](quinolinyl) interactions to consolidate the three-dimensional crystal. The dominance of the conventional hydrogen bonding in the molecular packing is confirmed by an analysis of the Hirshfeld surface.